Association of PCSK9 with platelet reactivity in patients with acute coronary syndrome treated with prasugrel or ticagrelor: The PCSK9-REACT study - Navarese, Eliano P.; Kolodziejczak, Michalina; Winter, Max-Paul; Alimohammadi, Arman; Lang, Irene M.; Buffon, Antonino; Lip, Gregory YH; Siller-Matula, Jolanta M. (International journal of cardiology, 2017)
Circulating proprotein convertase subtilisin/kexin type 9 (PCSK9) enzyme might be associated with increased activation of platelets. We aimed to assess the relationship between PCSK9 levels, platelet reactivity and ischemic outcomes. Consecutive ACS patients receiving prasugrel or ticagrelor and undergoing percutaneous coronary intervention (PCI) were enrolled in a prospective, observational study. Adenosine diphosphate (ADP)-induced platelet aggregation was determined by Multiplate Analyzer in the maintenance phase of treatment with prasugrel or ticagrelor. Major adverse cardiovascular events (MACEs) defined as composite of cardiovascular death, myocardial infarction, unstable angina, stent thrombosis, repeat revascularization, ischemic stroke were evaluated at 12months. A direct association was found between increased PCSK9 serum levels and platelet reactivity (r=0.30; p=0.004). When assessed according to tertile values of PCSK9, there was a significant increase in platelet reactivity in the upper vs lower tertile (p=0.02). Clinical outcome was available at follow-up in 178 subjects. In the upper PCSK9 tertile 13/59 (22.03%) patients experienced a clinical MACE at one year, vs 2/59 (3.39%) patients in the lower PCSK9 tertile. At one-year follow-up, PCSK9 was independently associated with increased ischemic MACEs: hazard ratio for upper vs lower PCSK9-level tertile was 2.62 (95% confidence interval 1.24–5.52; p=0.01). These findings suggest that increased PCSK9 levels are associated with higher platelet reactivity and are a possible predictor of ischemic events in ACS patients undergoing PCI.